2022
DOI: 10.3390/nu14040757
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Olive Oil and Its Components on Intestinal Inflammation and Inflammatory Bowel Disease

Abstract: With the rising global burden of inflammatory bowel disease (IBD) and the rising costs of novel biological drugs, there is an increasing need for dietary approaches and functional foods that could modulate the course of IBD. The Mediterranean diet has proven to be efficacious in managing chronic inflammatory diseases, and recent studies have also shown its benefits in the setting of IBD. Since olive oil and its compounds have been shown to provide a considerable anti-inflammatory effect, in this review, we aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 81 publications
1
22
0
Order By: Relevance
“…However, it is worth bearing in mind that the content of extra olive oil's bioactive compounds can differ between olive oils due to the environmental conditions, extraction procedures, harvesting handlings and storage. Therefore, good-quality, non-refined olive oils stored in cold, dark places (as well as in dark bottles) should be recommended [228].…”
Section: Is the Mediterranean Diet An Alternative To The Western Diet...mentioning
confidence: 99%
“…However, it is worth bearing in mind that the content of extra olive oil's bioactive compounds can differ between olive oils due to the environmental conditions, extraction procedures, harvesting handlings and storage. Therefore, good-quality, non-refined olive oils stored in cold, dark places (as well as in dark bottles) should be recommended [228].…”
Section: Is the Mediterranean Diet An Alternative To The Western Diet...mentioning
confidence: 99%
“…Yan et al 69 reported elevation of TBAR, IL-6, and INF-γ levels in colon tissue. These markers increase the inflammatory response of IL-6, INF-γ, NF-κB, destructive enzymes, and TBARs that cause damage to colon tissue 70 . In our study, CAPE significantly ameliorated tissue damage, IL-6, INF-γ, NF-κB, and TBARs in rats treated with DSS.…”
Section: Effect Of Cape and Sulfasalazine On Colonic Tbars Il-6 And I...mentioning
confidence: 99%
“…Olive oil, which is extracted from its fruit, is the most characteristic nutrient in this diet [ 8 ]. The beneficial effect of olive oil on health is well-established [ 9 , 10 , 11 , 12 ]. The helpful aspects of olive oil have commonly been attributed to its minor components, such as polyphenols, α-tocopherol, and other unsaponifiable compounds [ 8 , 13 , 14 ], but little attention has been paid to oleic acid (OA) (18:1 n-9 cis-9).…”
Section: Introductionmentioning
confidence: 99%